Integration of Islamic Values into English Language Teaching in the Digital Era: Challenges and Prospectives: Integrasi Nilai-Nilai Islam dalam Pengajaran Bahasa Inggris di Era Digital: Tantangan dan Prospek - Astuti, Ruli; Mustofa, M. Lutfi; Nisak, Nur Maslikhatun (Universitas Muhammadiyah Sidoarjo, 2024)
The development of technology in the digital era brings significant changes in everyday life, particularly in the area of education. On the other side, technological development has negative effects on the behavior of the young generation. As a result, real efforts are required, such as incorporating Islamic beliefs into English language at school. This study focuses at how to integrate Islamic values into English language learning in the digital era. This study conducts literature reviews using a number of sources, including papers and research journals from prior and recent relevant studies. This study reveals that the integration of Islamic values occurs in all phases of learning. The challenge in integrating Islamic values are not only from the teachers, but from students and parents. The prospective of integrating Islamic values in teaching and learning English in the digital era has a positive implication, including the use of technology in learning, cultural understanding, and theoretical and pedagogical aspects of learning. Keywords: Islamic Values, English Language Teaching, Digital Era